Does beetroot supplementation improve performance in combat sports athletes? A systematic review of randomized controlled trials - Delleli, S.; Ouergui, I.; Messaoudi, H.; Trabelsi, K.; Glenn, J. M.; Ammar, A.; Chtourou, H. (Nutrients, 2023)
While studies on dietary nitrate (NO3-) supplementation and its impact on combat sports performance are increasing, finite conclusions from currently available investigations remain unclear. Thus, the present systematic review examined the acute and chronic ergogenic effect(s) of dietary nitrate intake from beetroot on different aspects of combat sports performance. A systematic search for randomized placebo-controlled studies investigating the effects of beetroot supplementation on combat sports outcomes was performed through Scopus, PubMed/MEDLINE, Web of Science, Scielo, Sport Discus, and Cochrane Library databases up to 2 January 2023. The different terms related to beetroot and to combat sports were connected in the search strategies using the Boolean operators `AND` and `OR`. A total of nine studies with good methodological quality (based on the Cochrane risk of bias tool) fulfilled the inclusion criteria. Seven studies used an acute supplementation strategy, while the other two studies utilized chronic supplementation. Findings showed beetroot intake may be an effective tool to improve oxidative metabolism and muscle force production (i.e., isokinetic and isometric) in combat sports athletes. However, these effects may depend on the population, intake duration, muscle group activated, and exercise type. Future studies are required to (1) understand the effects on female athletes and (2) elucidate the impacts of dosing protocols and specific exercise modalities for enhancing combat sports performance.